Mechanochemical synthesis of PZT powders - Brankovic, Z.; Brankovic, G.; Jovalekic, C.; Maniette, Y.; Cilense, M.; Varela, José Arana [UNESP] (Elsevier B.V., 2003)
PZT ceramic powders were successfully prepared from the mixture of PbO, ZrO2 and TiO2 by mechanochemical synthesis in a planetary ball mill, under different milling conditions. Phase evolution during synthesis was monitored by X-ray diffraction analysis. Intensive milling resulted in formation of the nanocrystalline, perovskite PZT powders after 1 h of milling. This is a significant improvement in comparison to milling conditions reported by other authors. Depending on milling parameters the presence of some other phases, such as unreacted ZrO2, was also detected in some samples. The changes in powder size and morphology due to intensive milling, were determined by SEM and TEM, while BET analysis was used to determine specific surface area of the powders. Conclusions about processes taking place during mechanochemical synthesis of PZT powders were made based on the results of characterization. (C) 2002 Elsevier B.V. B.V. All rights reserved.
Keywords: mechanochemical synthesis; PZT; milling parameters; planetary ball mill